2021
DOI: 10.1038/s41598-021-84660-5
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of tuna hydrolysate and insect larvae improves fishmeal replacement efficacy of poultry by-product in Lates calcarifer (Bloch, 1790) juveniles

Abstract: The effects of feeding different levels of poultry by-product meal (PBM) replacing fishmeal (FM) protein, supplemented with tuna hydrolysate (TH) and Hermetia illucens (HI) larvae, on the growth, fillet quality, histological traits, immune status, oxidative biomarker levels and gut microbiota of juvenile barramundi, Lates calcarifer were investigated for six weeks. Barramundi were fed four isonitrogenous and isolipidic diets in which a FM based diet was used as the Control diet (Diet1) and compared with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 140 publications
5
35
1
Order By: Relevance
“…This result is in agreement with Chaklader et al (2020), where the addition of FPH in diets abundant in poultry by-product meal significantly increased MUFA and PUFA content when compared to the control. Feeding excessive levels of alternate FM protein diets negatively impacted the concentration of healthpromoting fatty acids such EPA and DHA in barramundi (Chaklader et al, 2021) and juvenile totoaba, Totoaba macdonaldi (Zapata et al, 2016). However, in the present study total PUFA, Σn-3, Σn-6, Σn-9…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…This result is in agreement with Chaklader et al (2020), where the addition of FPH in diets abundant in poultry by-product meal significantly increased MUFA and PUFA content when compared to the control. Feeding excessive levels of alternate FM protein diets negatively impacted the concentration of healthpromoting fatty acids such EPA and DHA in barramundi (Chaklader et al, 2021) and juvenile totoaba, Totoaba macdonaldi (Zapata et al, 2016). However, in the present study total PUFA, Σn-3, Σn-6, Σn-9…”
Section: Discussioncontrasting
confidence: 70%
“…piscicida, and V. anguillarum (Costa et al, 2020). Similarly, a number of studies supplementing FPH have shown the modulation of disease resistance against pathogenic bacteria in barramundi (Chaklader et al, 2021;Siddik et al, 2021), red sea bream, Pagrus major (Bui et al, 2014;Khosravi et al, 2015) and European sea bass (Kotzamanis et al, 2007). In the present study, the improved infection rate against V. harveyi in the test diets could be due to the presence of bioactive peptides in FPH.…”
Section: Discussionsupporting
confidence: 59%
“…Regarding the muscle FA profile, an increase in total SFA in the muscle of barramundi fed with 80PBM-20HI and 75PBM-25HI was due to the substantial increase in lauric acid (C12:0) and myristic acid (C14:0). The HI larvae meal is a rich source of C12:0 and C14:0 which have been reported to enhance the total SFA concentration in barramundi ( 23 , 24 ) and other fish species such as Siberian sturgeon, Acipenser baerii ( 58 ), rainbow trout ( 59 ), and Eurasian perch, Perca fluviatilis ( 60 ). Oleic acid plus elaidic acid (C18: 1cis + trans), causing a higher concentration of MUFA in PBM-HI-based diets clearly improved the MUFA concentration of barramundi in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the potentiality of an ingredient cannot be solely evaluated by the effects on growth and other physiological and immunological parameters as dietary alteration may stimulate alteration in organoleptic characteristics and other biochemical composition functions of fish filets. The exclusive or complete inclusion of animal protein ingredients such as PBM or meat meal had no effect on the barramundi filet texture and color ( 24 , 25 ) though female tenches, Tinca tinca filet quality was impacted by PBM ( 26 ). Except for filet organoleptic characteristics, PBM alone reduced the retention of nutrient composition such as essential amino acid and fatty acid for barramundi ( 27 , 28 ), however, such effects were not observed for other species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation